Pemberdayaan Hak-Hak Perempuan Berdasarkan Konsep HAM di Jorong Lundang Kecamatan Ampek Angkek Kabupaten Agam - Fauhatun, Fathin; Anggraini, Reni Dian; Fitrawati, Fitrawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This paper discusses the Empowerment of Women's Rights in Lundang and the Purpose of Empowering Women's Rights Based on the Concept of Human Rights in Jorong Lundang. The purpose of this study is to reveal or describe how women's rights are empowered and the purpose of this empowerment is based on the concept of human rights in Lundang. The method used by the author in this study is a qualitative method, namely a research method carried out by observation and interviews while the approach used is snowball sampling. The results of this study show that in realizing gender equality, one of them is by mainstreaming the empowerment of women's rights in Lundang, we can see this empowerment that Lundang women are no longer only involved in the domestic world but have also entered the public sphere, namely working as one of the by establishing the Panjaik Patah Sulaman Gallery house and forming PKK activities as a forum to increase women's creativity and self-confidence so that no more women are intimidated and banned from working in Lundang.